Nutrient regulation of human intestinal sugar transporter (SGLT1) expression. Issue 1 (July 1997) - Dyer, J; Hosie, K B; Shirazi-Beechey, S P
Abstract : BACKGROUND: The activity of most intestinal nutrient transporters is adaptively regulated by the type and amounts of nutrients entering the intestinal lumen. The concentration and activity of the intestinal Na+/glucose cotransporter (SGLT1) are regulated by dietary sugars in most animal species. The activity and abundance of SGLT1 in biopsy specimens removed from human jejunal regions exposed to, and having limited access to, luminal nutrients have been measured and compared. AIMS: To study the effects of luminal nutrients on the expression of SGLT1 in the human intestine. PATIENT AND METHODS: Brush border membrane vesicles (BBMV) were prepared from biopsy specimens removed from the intestine of a 50 year old man who had developed a high output jejunal fistula, and adjacent mucosal fistula, a condition present for 12 months after surgery for a strangulated hernia. BBMV prepared from intestine exposed to luminal nutrients, and from dysfunctional intestine with a limited exposure to nutrients, were used to measure Na+ dependent glucose transport and abundance of SGLT1 protein. RESULTS: The levels of SGLT1 activity and abundance in the BBMV prepared from control biopsy specimens were similar to those found in BBMV prepared from the intestine of healthy individuals. BBMV from the dysfunctional intestine, exposed to limited levels of luminal nutrients, had reduced levels of SGLT1 activity. This reduction in SGLT1 activity and abundance was above that associated with any villus atrophy, as assessed by the abundance/activity of lactase and villin concentrations. CONCLUSIONS: These data indicate that the activity and expression of SGLT1 in human intestine is maintained by the presence of luminal nutrients.